2013
DOI: 10.1111/cp.12010
|View full text |Cite
|
Sign up to set email alerts
|

Objectification Theory: Of relevance for eating disorder researchers and clinicians?

Abstract: Background There is a large and expanding body of research on Objectification Theory. Central to the theory is the proposition that self‐objectification results in shame and anxiety surrounding the body, and as a consequence, the development of eating disorders. However, the theory and research have been developed and reported in the gender and social psychological literatures rather than the clinical literature. Accordingly, the goal of this article is to present an account of Objectification Theory to a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
80
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 89 publications
3
80
0
3
Order By: Relevance
“…Indeed, the literature has often equated body surveillance with self-objectification using these constructs interchangeably [32,34]. Nevertheless, some researchers describe these constructs as somewhat distinct but highly related [39].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the literature has often equated body surveillance with self-objectification using these constructs interchangeably [32,34]. Nevertheless, some researchers describe these constructs as somewhat distinct but highly related [39].…”
Section: Methodsmentioning
confidence: 99%
“…The most recent and comprehensive metaanalysis of experimental studies [26] demonstrated that media-idealized images have the most harmful and substantial impact on vulnerable individuals (i.e., "internalizers" and "self-objectifiers"), regardless of media characteristics (i.e., frequency and length of exposure, media types) or gender. Although media-ideal internalization and selfobjectification processes constitute two principal socialcognitive mechanisms through which media-idealized images exert their long-term influence on negative bodyfeelings and eating disturbances [17,[27][28][29][30][31][32][33], there remains a strong need for prospective research on their effects in developmentally appropriate samples [26][27][28][29][30][31][32][33][34]. In the current study, we aim to fill this gap in the literature, drawing upon objectification theory [35] to provide us with a testable framework for the proposed links.…”
mentioning
confidence: 99%
See 3 more Smart Citations